1991
DOI: 10.1002/pd.1970110202
|View full text |Cite
|
Sign up to set email alerts
|

Fetal echocardiography using transvaginal and transabdominal probes during the first period of pregnancy: A comparative study

Abstract: The authors compare the diagnostic possibilities of fetal transabdominal echocardiography versus transvaginal echocardiography. A larger diagnostic capacity is verified in different gestation ages with transvaginal probe between the 11th and 14th week of gestation. The results are emphasized by colour Doppler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…Both techniques were comparable at 14 weeks of gestation, after that period transabdominal sonography accurately demonstrated the structures of the fetal heart, but in overweight patients the transvaginal sonography was a complementary method. Similar results were published by D'Amelio et al [33]. Achiron and Tadmor [34] found out that the transvaginal sonography was more sensitive than the transabdominal sonography in the diagnosis of fetal abnormalities between 9 and 13 weeks of gestation.…”
Section: Discussionsupporting
confidence: 80%
“…Both techniques were comparable at 14 weeks of gestation, after that period transabdominal sonography accurately demonstrated the structures of the fetal heart, but in overweight patients the transvaginal sonography was a complementary method. Similar results were published by D'Amelio et al [33]. Achiron and Tadmor [34] found out that the transvaginal sonography was more sensitive than the transabdominal sonography in the diagnosis of fetal abnormalities between 9 and 13 weeks of gestation.…”
Section: Discussionsupporting
confidence: 80%
“…Although earlier visits have been tried in different studies, but all are fetal echocardiography for the risky fetuses only, D'Amelio et al studied it at 11-14 weeks, Dolkart and Reimers studied it at 10-15 weeks of gestation and this is for helping in earlier termination of pregnancy as up to 75 % of parents chose that in U.K. where termination of pregnancy is allowed up to 23 weeks but all have concluded that it can never be a practical routine way of antenatal cardiac screening, as it always needs another confirmative study at 18-22 weeks because it was found that minor CHDs were not all correctly early detected. [21][22][23] We calculated the specificity, sensitivity and accuracy of the 18-22 weeks views with antenatal and postnatal echocardiography (which is the most accurate), and to compare these results with other studies' results was very difficult as most studies are about the detailed echocardiography which is done only for the risk patients, and mostly they were done by cardiologists, but we found nearly similar study of Randall et al who reported wide range from 35% up to 86%,while in this study, the accuracy was in the high risk group 96% antenatally and 96% postnatally, and in the low risk group was 100% antenatally and 98% postnatally differing according to scanning regimen, operators' skills and equipment. 24 While our results are similar to study done on fetal detailed echocardiography of Berkely et al who stated his results' accuracy about 97% (94.3-99.0%) but he only calculated it postnatally and from this we deduce that the cardiac scanning is of high accuracy which promotes it to be in the routine screening of all cases, but this is in agreement with Randall et al who didn't support the routine use of fetal echocardiography by cardiologists in the second trimester among unselected and low risk population as it is not cost effective.…”
Section: Discussionmentioning
confidence: 99%
“…Resources for counselling after termination are inadequate and many parents feel unsupported. 39 In future transvaginal echocardiography may offer an earlier diagnosis40 41 but it may never be a practical routine alternative despite the advantage of termination at 12-14 weeks.…”
mentioning
confidence: 99%